A high entropy alloy coating for shielding high-energy electrons and its preparation method and application

By using high-entropy alloy coatings in the aerospace and nuclear industries, the problem of device failure caused by high-energy electron irradiation is solved, improving the radiation shielding capability of the matrix and ensuring the stable operation of electronic devices.

CN118291966BActive Publication Date: 2025-01-24HARBIN INST OF TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410342505.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-25
Publication Date
2025-01-24
Estimated Expiration
2044-03-25

AI Technical Summary

Technical Problem

In the existing aerospace and nuclear industry fields, the problem of device failure caused by high-energy electronic radiation has not been effectively solved.

Method used

Using a high-entropy alloy coating, aluminum powder, chromium powder, iron powder, vanadium powder and tungsten powder are mixed at a specific molar ratio, and a high-entropy alloy coating with a single BCC solid solution structure is prepared on the surface of the substrate using laser cladding technology. To improve the radiation shielding ability of the matrix.

Benefits of technology

Effectively improve the radiation shielding ability of the substrate material, ensure the stable operation of electronic devices in high -energy electron radiation environments, and improve the mechanical properties and high temperature stability of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118291966B_ABST
    Figure CN118291966B_ABST
Patent Text Reader

Abstract

The present invention discloses a high entropy alloy coating for shielding high-energy electrons and a preparation method and application thereof, belonging to the technical field of radiation-resistant metal materials. The present invention solves the problem of device failure caused by high-energy electron irradiation in the existing aerospace and nuclear industries. The present invention uses laser cladding technology to prepare AlCrFeVW with a single BCC phase structure on the surface of a ferrite / martensitic steel substrate. x High entropy alloy protective coatings effectively improve the radiation shielding ability of the base material while ensuring that the overall density does not change much, thereby ensuring the stable operation of electronic devices. In addition, the coating and the base metallurgical bonding is good, the coating organization is uniform and the structure is stable, there is no crack on the surface, and it presents a good macroscopic morphology. It has excellent mechanical properties and strong high temperature stability, and can meet the conditions for long-term use in extreme environments, and has broad development potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-entropy alloy coating for shielding high-energy electrons and a preparation method and application thereof, belonging to the technical field of radiation-resistant metal materials. Background Art

[0002] In recent years, the rapid development of the aerospace industry has put forward higher requirements for the safety and stability of spacecraft. The space electronic radiation environment is one of the important environmental factors faced by spacecraft in orbit, and it is also an important cause of abnormalities or failures of aerospace electronic components. Researchers have developed radiation shielding materials such as concrete, polymers, and metals. However, traditional materials have limitations, such as the high specific gravity of concrete and the toxicity of lead. Therefore, the development of new radiation shielding materials with non-toxicity, low density, good shielding effect, and excellent physical properties has become an important measure to promote the development of my country's aerospace industry.

[0003] High entropy alloys are mainly composed of at least five basic elements mixed at a molar concentration of 5 to 35%. They have special characteristics such as high strength and thermal stability, good fatigue resistance, high fracture and corrosion resistance, and radiation stability, and are expected to become a new generation of radiation shielding materials. High entropy alloys generally exhibit excellent high-temperature strength and creep resistance. Their increased composition flexibility provides a unique opportunity to design advanced radiation shielding alloys. They have a unique atomic structure and high configurational entropy, so they have stronger resistance to radiation damage than traditional alloys. Therefore, it is necessary to provide a high entropy alloy that can shield high-energy electrons. Summary of the invention

[0004] In order to solve the problem of device failure caused by high-energy electron irradiation faced in the existing aerospace and nuclear industries, the present invention provides a high-entropy alloy coating for shielding high-energy electrons, a preparation method and an application thereof.

[0005] The technical solution of the present invention:

[0006] One of the purposes of the present invention is to provide a high entropy alloy coating for shielding high-energy electrons. The high entropy alloy coating is composed of aluminum powder, chromium powder, iron powder, vanadium powder and tungsten powder in a molar ratio of 5:5:5:5:(0-5) by weight.

[0007] It is further defined that the aluminum powder, chromium powder, iron powder, vanadium powder and tungsten powder are in a molar ratio of 5:5:5:5:1.

[0008] It is further defined that the aluminum powder, chromium powder, iron powder, vanadium powder and tungsten powder are in a molar ratio of 5:5:5:5:2.

[0009] It is further defined that the aluminum powder, chromium powder, iron powder, vanadium powder and tungsten powder are in a molar ratio of 5:5:5:5:3.

[0010] It is further defined that the aluminum powder, chromium powder, iron powder, vanadium powder and tungsten powder are in a molar ratio of 5:5:5:5:4.

[0011] It is further defined that the particle size of aluminum powder, chromium powder, iron powder, vanadium powder and tungsten powder is less than 53 μm.

[0012] It is further defined that the mass purity of aluminum powder, chromium powder, iron powder, vanadium powder and tungsten powder is ≥ 99.5%.

[0013] It is further defined that the high entropy alloy coating is a single BCC solid solution structure.

[0014] The present invention provides a method for preparing the above-mentioned high entropy alloy coating, the method comprising the following steps:

[0015] (1) Aluminum powder, chromium powder, iron powder, vanadium powder and tungsten powder are mixed in proportion, placed in a ball mill, stearic acid is used as a process control agent, zirconium oxide balls are added for ball milling, and alloy powder is obtained;

[0016] (2) After the alloy powder is dried, it is spread flat on a substrate to obtain a prefabricated metal powder layer, and then the prefabricated metal powder layer is subjected to laser cladding treatment, cooled at room temperature, and ground and polished to obtain a high entropy alloy coating that shields high-energy electrons.

[0017] It is further defined that the ball milling conditions in (1) are: ball-to-material ratio of 20:1, ball milling speed of 800 r / min, and ball milling time of 20 h.

[0018] It is further defined that the amount of stearic acid added in (1) is 5 wt.%.

[0019] It is further defined that the alloy powder in (2) is vacuum dried at 80° C. for 6 h.

[0020] It is further defined that the thickness of the prefabricated metal powder layer in (2) is 2-4 mm.

[0021] It is further defined that the laser cladding treatment conditions in (2) are: laser power 2000-4000 W, scanning rate 10 mm / s, spot diameter 2 mm, tower connection rate 50%, and protective gas is argon.

[0022] It is further defined that the grinding process in (2) is: grinding with sandpapers of 100 mesh, 400 mesh, 800 mesh, 1500 mesh and 2000 mesh in sequence.

[0023] It is further defined that the polishing treatment in (2) is: polishing using 5000 mesh and 10000 mesh polishing paste.

[0024] It is further defined that in (2), the matrix is ​​ferrite / martensitic steel.

[0025] Further, in (2), before the substrate is used

[0026] A third object of the present invention is to use the above-mentioned high entropy alloy coating in high-energy electron radiation protection.

[0027] Beneficial effects:

[0028] The present invention adopts laser cladding technology to prepare AlCrFeVW on the surface of the substrate x High entropy alloy protective coating can improve the radiation shielding ability of the substrate and ensure that the device operates well in a high-energy electron radiation environment. Compared with the existing technology, it has the following advantages:

[0029] (1) The present invention uses laser cladding technology to prepare AlCrFeVW with a single BCC phase structure on the surface of a ferrite / martensitic steel matrix. x High entropy alloy protective coatings effectively improve the radiation shielding ability of the base material while ensuring that the overall density does not change much, thereby ensuring the stable operation of electronic devices. In addition, the coating and the base metallurgical bonding is good, the coating organization is uniform and the structure is stable, there is no crack on the surface, and it presents a good macroscopic morphology. It has excellent mechanical properties and strong high temperature stability, and can meet the conditions for long-term use in extreme environments, and has broad development potential.

[0030] (2) The present invention utilizes the flexible composition of high entropy alloys and selects a high entropy alloy element design concept of high / low atomic number combination, combining high atomic number element W, medium atomic number elements Cr, Fe, V and low atomic number element Al. The high atomic number element W has good shielding properties of high-energy electrons and gamma ray radiation; the medium atomic number element V can improve the mechanical properties of the alloy and reduce coating cracks; the Cr element can improve corrosion resistance and oxidation resistance; the Fe element not only stabilizes the BCC structure, but also has the effect of reducing costs; and the low atomic number element Al is a low radiation energy loss component. The present invention prepares AlCrFeVW on the surface of ferrite / martensitic steel by laser cladding technology. x High-entropy alloy coatings improve the high-energy electron shielding performance of structural materials. After high-energy electrons are injected into high-entropy alloy coatings, they first react with low-atomic-number elements to reduce the primary electron energy and produce less bremsstrahlung. High-atomic-number elements have a larger scattering cross section and can absorb bremsstrahlung photons. The combination of elements with different atomic numbers can improve the radiation shielding performance of materials and effectively improve the radiation shielding ability of the base material, thereby ensuring the stable operation of electronic devices in complex radiation environments. In addition, due to its unique atomic structure and high configuration entropy, the structure of high-entropy alloys itself has a stronger ability to resist radiation damage than traditional alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1AlCrFeVW prepared in Example 1 0.2 SEM image of alloy metal powder;

[0032] Figure 2 AlCrFeVW prepared in Examples 1 to 5 x XRD test results of high entropy alloy coating;

[0033] Figure 3 AlCrFeVW prepared in Example 1 0.2 SEM images of high entropy alloy coatings (different magnifications);

[0034] Figure 4 AlCrFeVW prepared in Examples 1 to 5 x Comparison chart of hardness test results of high entropy alloy coating surface;

[0035] Figure 5 The radiation protection performance simulation test diagram of the samples prepared in Examples 1 to 5;

[0036] Figure 6 This is the XRD test result diagram of the FeCrVW high entropy alloy coating prepared in Comparative Example 1;

[0037] Figure 7 This is a physical photo of the FeCrVW high entropy alloy coating prepared in Comparative Example 1. DETAILED DESCRIPTION

[0038] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0039] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0040] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0041] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0042] Example 1

[0043] (1) Pretreatment of metal powder

[0044] AlCrFeVW was prepared according to the molar ratio (Al:Cr:Fe:V:W=5:5:5:5:1). 0.2 High entropy alloy metal powder ratio, use an electronic balance to weigh the single metal powder. The source of the metal powder is shown in Table 1 below:

[0045] Table 1 Summary of reagents and raw materials used in the experiment

[0046] name Molecular formula purity Particle size / μm Manufacturer Iron Fan Fe 99.5% 18-53 Zhongnuo New Materials Technology Co., Ltd. Chrome powder Cr 99.5% 18-53 Zhongnuo New Materials Technology Co., Ltd. Tungsten powder W 99.5% 18-53 Zhongnuo New Materials Technology Co., Ltd. Aluminum powder Al 99.5% 18-53 Zhongnuo New Materials Technology Co., Ltd. Vanadium powder V 99.5% 18-53 Zhongnuo New Materials Technology Co., Ltd.

[0047] The weighed aluminum powder, chromium powder, iron powder, vanadium powder and tungsten powder were mixed and placed in a ball mill. Stearic acid was used as a process control agent. Zirconia balls were added for ball milling. The ball-to-material ratio was 20:1, the ball milling speed was 800r / min, and the ball milling time was 20h to obtain AlCrFeVW 0.2 Alloy metal powder.

[0048] (2) Treatment of ferrite / martensitic steel metal matrix

[0049] The surface of the substrate ferrite / martensitic steel was polished to 800 mesh using a metallographic polishing machine to remove oxides on the substrate surface, and then washed three times with anhydrous ethanol and acetone and dried naturally for later use.

[0050] (3) Drying of high entropy alloy powder: The AlCrFeVW prepared in step (1) is dried in a vacuum oven. 0.2 The high entropy alloy powder was dried at a temperature of 60°C and a drying time of 8 h.

[0051] (4) Laser cladding preparation of high entropy alloy coating

[0052] The dried AlCrFeVW 0.2 The alloy metal powder is spread on the surface of the ferrite / martensitic steel substrate, with a powder thickness of 2 mm. The coating is prepared using laser cladding technology, with a laser power of 2000 W, a scanning rate of 10 mm / s, a spot diameter of 2 mm, a tower connection rate of 50%, and an argon gas as the protective gas. After the cladding is completed, the material is placed at room temperature to cool. The coating is polished with 100 mesh, 400 mesh, 800 mesh, 1500 mesh, and 2000 mesh sandpaper in turn, and polished with 5000 mesh and 10000 mesh polishing pastes, and a mirror surface is presented after polishing.

[0053] The dried high entropy alloy metal powder obtained in Example 1 was observed by scanning electron microscopy. The alloy powder eventually formed a structure with uniform particle size and stable composition, such as Figure 1As shown, the final alloy powder has a particle size of 1-5 μm.

[0054] The phase structure of the high entropy alloy coating obtained in Example 1 was characterized. 0.2 The XRD test results of high entropy alloy coating are as follows: Figure 2 MediumAlCrFeVW 0.2 As shown in the curve, the coating exists in a single BCC solid solution phase structure.

[0055] The AlCrFeVW obtained in Example 1 0.2 The surface microstructure of the high entropy alloy coating was characterized by scanning electron microscopy (SEM) images. Figure 3 As shown in the figure, the coating has a good macroscopic morphology, without obvious cracks and pores. The coating is composed of a hypoeutectic structure consisting of dark gray grain boundaries, dark gray regional cellular eutectics and fine dispersed blocky particles. The fine dispersed blocky particles are MC ceramic particles formed by the reaction of the process control agent (stearic acid) introduced during the ball milling process and the metal, and they mainly exist at the grain boundaries.

[0056] The microhardness of the laser cladding high entropy alloy coating in Example 1 was measured using a microhardness tester. The results are as follows: Figure 4 Middle W 0.2 As shown, the average hardness of the alloy coating is 471.4 HV, which is higher than the hardness of the substrate (235.7 HV).

[0057] Example 2

[0058] The difference between this embodiment and embodiment 1 is that: in (1), AlCrFeVW is prepared according to the molar ratio (Al:Cr:Fe:V:W=5:5:5:5:2). 0.2 High entropy alloy metal powder ratio; (4) the laser power is 2500W; the remaining process steps and parameter settings are the same as in Example 1, to obtain AlCrFeVW 0.4 Alloy Metal Powder and AlCrFeVW 0.4 High entropy alloy coating.

[0059] The phase structure of the high entropy alloy coating obtained in Example 2 was characterized. 0.4 The XRD test results of high entropy alloy coating are as follows: Figure 2 MediumAlCrFeVW 0.4 As shown in the curve, the coating exists in a single BCC solid solution phase structure without obvious second phase peak.

[0060] The microhardness of the laser cladding high entropy alloy coating in Example 2 was measured using a microhardness tester. The results are as follows: Figure 4 Middle W 0.4As shown, the average hardness of the alloy coating is 515.0 HV, which is higher than the hardness of Example 1 (471.4 HV).

[0061] Example 3

[0062] The difference between this embodiment and embodiment 1 is that: in (1), AlCrFeVW is prepared according to the molar ratio (Al:Cr:Fe:V:W=5:5:5:5:3). 0.6 High entropy alloy metal powder ratio; (4) the laser power is 3000W; the remaining process steps and parameter settings are the same as in Example 1, to obtain AlCrFeVW 0.6 Alloy Metal Powder and AlCrFeVW 0.6 High entropy alloy coating.

[0063] The phase structure of the high entropy alloy coating obtained in Example 3 was characterized. 0.6 The XRD test results of high entropy alloy coating are as follows: Figure 2 MediumAlCrFeVW 0.6 As shown in the curve, the coating exists in a single BCC solid solution phase structure. Compared with the curve of Example 1, the (110) crystal plane of the BCC phase moves in the direction of small 2θ. This is because W with a larger atomic radius leads to a single phase AlCrFeVW x The interplanar spacing of the BCC structure in the HEAs coatings is enlarged, causing the crystal planes to move toward the low 2θ direction with increasing W concentration.

[0064] The microhardness of the laser cladding high entropy alloy coating in Example 2 was measured using a microhardness tester. The results are as follows: Figure 4 Middle W 0.6 As shown, the average hardness of the alloy coating is 561.0 HV, which is higher than the hardness of Example 2 (515.0 HV).

[0065] Example 4

[0066] The difference between this embodiment and embodiment 1 is that: in (1), AlCrFeVW is prepared according to the molar ratio (Al:Cr:Fe:V:W=5:5:5:5:4). 0.8 High entropy alloy metal powder ratio; (4) the laser power is 3500W; the remaining process steps and parameter settings are the same as in Example 1, to obtain AlCrFeVW 0.8 Alloy Metal Powder and AlCrFeVW 0.8 High entropy alloy coating.

[0067] The phase structure of the high entropy alloy coating obtained in Example 4 was characterized. 0.8 The XRD test results of high entropy alloy coating are as follows: Figure 2MediumAlCrFeVW 0.8 As shown in the curve, the coating exists in a single BCC solid solution phase structure.

[0068] The microhardness of the laser cladding high entropy alloy coating in Example 4 was measured using a microhardness tester. The results are as follows: Figure 4 Middle W 0.8 As shown, the average hardness of the alloy coating is 609.6 HV, which is higher than the hardness of Example 3 (561.0 HV).

[0069] Example 5

[0070] The differences between this embodiment and Embodiment 1 are as follows: (1) the AlCrFeVW1 high entropy alloy metal powder is proportioned according to the molar ratio (Al:Cr:Fe:V:W=5:5:5:5:5); (4) the laser power is 4000 W; the remaining process steps and parameter settings are the same as those in Embodiment 1, and AlCrFeVW1 alloy metal powder and AlCrFeVW1 high entropy alloy coating are obtained.

[0071] The physical structure of the high entropy alloy coating obtained in Example 5 was characterized. The XRD test results of the specific AlCrFeVW1 high entropy alloy coating are as follows: Figure 2 As shown in the AlCrFeVW1 curve, the coating exists in a single BCC solid solution phase structure.

[0072] The microhardness of the laser cladding high entropy alloy coating in Example 5 was measured using a microhardness tester. The results are as follows: Figure 5 As shown in Figure 1, the average hardness of the alloy coating is 671.0 HV, which is higher than all other coatings. This is because the increase in W content enhances the hardness of the HEAs coating, which is attributed to the increased covalency within the HEAs due to the high valence electron density.

[0073] The radiation protection performance of the high entropy alloy coatings prepared in Examples 1 to 5 was simulated and tested. Geant4 simulations were performed on electron sources of different energies using the high entropy alloy materials. The specific test results are shown in Figure 5 .Depend on Figure 5 It can be seen that the shielding ability of the high entropy alloy coating for electrons far exceeds that of the ferrite / martensitic steel matrix, and is improved by 67% compared to the matrix material under the same thickness.

[0074] Comparative Example 1

[0075] The difference between this comparative example and Example 1 is that: in (1), the CrFeVW high entropy alloy metal powder is proportioned according to the molar ratio (Al:Cr:Fe:V:W=0:5:5:5:5), and the remaining process steps and parameter settings are the same as those in Example 1, to obtain CrFeVW alloy metal powder and CrFeVW high entropy alloy coating.

[0076] The physical structure of the high entropy alloy coating obtained in this comparative example was characterized. The specific XRD test results of the CrFeVW high entropy alloy coating are as follows: Figure 6 As shown, the coating failed to form a solid solution phase.

[0077] Further observations such as Figure 7 From the surface of the CrFeVW high entropy alloy coating shown, it can be seen that a large number of cracks appear in the alloy coating and the surface quality of the coating is poor. This is mainly because the alloy coating fails to form a solid solution phase and there are a large number of intermetallic compounds (brittle phases) in the alloy coating, which seriously affects the mechanical properties of the coating. Therefore, the coating is brittle, extremely hard and extremely poor in toughness.

[0078] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A high entropy alloy coating for shielding high-energy electrons, characterized in that: The high entropy alloy coating is composed of aluminum powder, chromium powder, iron powder, vanadium powder and tungsten powder in a molar ratio of 5:5:5:5:(1-5) by weight; The high entropy alloy coating has a single BCC solid solution structure.

2. The high entropy alloy coating according to claim 1, characterized in that: The molar ratio of aluminum powder, chromium powder, iron powder, vanadium powder and tungsten powder is 5:5:5:5:

2.

3. The high entropy alloy coating according to claim 1, characterized in that: The molar ratio of aluminum powder, chromium powder, iron powder, vanadium powder and tungsten powder is 5:5:5:5:

3.

4. The high entropy alloy coating according to claim 1, characterized in that: The molar ratio of aluminum powder, chromium powder, iron powder, vanadium powder and tungsten powder is 5:5:5:5:

4.

5. A method for preparing a high entropy alloy coating according to any one of claims 1 to 4, characterized in that: include: (1) Aluminum powder, chromium powder, iron powder, vanadium powder and tungsten powder are mixed in proportion, placed in a ball mill, stearic acid is used as a process control agent, zirconium oxide balls are added for ball milling, and alloy powder is obtained; (2) After the alloy powder is dried, it is spread flat on a substrate to obtain a prefabricated metal powder layer, and then the prefabricated metal powder layer is subjected to laser cladding treatment, cooled at room temperature, and ground and polished to obtain a high entropy alloy coating that shields high-energy electrons.

6. The preparation method according to claim 5, characterized in that: (1) The ball milling conditions are as follows: ball-to-material ratio is 20:1, ball milling speed is 800 r / min, and ball milling time is 20 h.

7. The preparation method according to claim 6, characterized in that: (2) The laser cladding treatment conditions are: laser power 2000-4000W, scanning rate 10mm / s, spot diameter 2mm, tower connection rate 50%, and protective gas is argon.

8. Use of the high entropy alloy coating as claimed in any one of claims 1 to 4 in high energy electron radiation protection.

Citation Information

Patent Citations

  • High-powder-yield mechanical alloying and sintering forming method for high-entropy alloy

    CN113528925A

  • Wear-resistant high-entropy alloy coating for material surface protection and preparation method of wear-resistant high-entropy alloy coating

    CN115852361A